Investigating the required competencies of valuation surveying graduates - Jiram, W. R. A. (CRC Press/Balkema, 2016)
An investigation into the views of industry, academia and professional body on valuation surveying education revealed there is a considerable gap in the expectation of graduate competency and achievement of it. This paper presents the qualitative evaluation to determine the competencies that need to be acquired by valuation graduates. This was accomplished by collecting interview protocol from a sample of 16 experts consisting of academics, industry, and professional body representatives to provide a full picture of the extent of coverage of competencies of valuation surveying graduates. The participant experience years range from 15 to 45 years (M = 29.83, SD = 10.92). A text/thematic analysis was used to get the dimensions of VS graduate competencies. Further investigation and validation for the competency dimensions of valuation graduates is needed to provide adequate exploration.